Very high cycle fatigue durability of an additively manufactured single-crystal Ni-based superalloy - Bortoluci Ormastroni, Luciana Maria; Lopez-Galilea, Inmaculada; Pistor, Julian; Ruttert, Benjamin; Körner, Carolin; Theisen, Werner; Villechaise, Patrick; Pedraza, Fernando; Cormier, Jonathan (Additive Manufacturing, 2022)
A single crystalline (SX) nickel-based superalloy additively manufactured (AM) by electron beam-based powder bed fusion (PBF-E) was investigated under very high cycle fatigue (VHCF) at 1,000 °C in fully reversed conditions (Rε = −1). Specimens processed using a classical Bridgman solidification route and the impact of a hot isostatic pressing (HIP) treatment were also considered. It is shown that the fatigue lifetime of the AM specimens is higher or in the same range of the Bridgman processed ones with the same chemical composition. All defect-free AM samples fail by surface initiation with very long VHCF lives. In the absence of metallurgical defects such as grain boundaries or pores, the superalloy chemical stability against oxidation governs VHCF failure.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Additive manufacturing; Electron beam-based powder bed fusion; Nickel-based superalloys; Very high cycle fatigue